TEATER TANAH IBU: MATRILINEAL DAN KUASA IDEOLOGI KAUM PEREMPUAN MINANGKABAU - Saaduddin - (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
theatre performance contains various ideologies that are promoted by the director as a choice of his workmanship. Thisideology can be seen in the relationship between the text of the script and the performance text. In Teater Tanah Ibu, a workby director Syuhendri, the background of Minangkabau culture is used as the centre of development for the dramatic elementsof the performance that are generated by the role of the women in the performance, and as such, the messages conveyed are fullof the ideology and the message of women’s resistance to the hegemony of Minangkabau men. This paper uses a multidisciplinaryapproach and aims to outline: (1) the process of creating Teater Tanah Ibu and (2) the form of women’s ideologyfound in Teater Tanah Ibu. The observation showed that the ideology of Minangkabau women in Teater Tanah Ibu was bornas the dialectic of women in understanding a migrant culture that reflects women’s ideology.Keywords: Teater Tanah Ibu, Ideology, Women